(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
It is a phrase that refers to the process of developing and implementing advertising plans inconsideration of quantitative and qualitative client data obtained through digital analytics as well as othersources. All of these many aspects of marketing form an intertwined and interdependent web. Businessesand online merchants who want to get off to a solid start and stay ahead of the competition are required toadopt data-driven marketing tactics that are at the leading edge. Because of this, data-driven marketinghas gained a lot of traction in recent years. Not only can data-driven marketing improve conversion rates,but it also enables marketers to create more engaging campaigns and, most importantly, to increase theamount of money they generate from online sales. First things first in order for companies to properlypitch their commodities to prospective buyers, they need to amass pertinent information on those buyers.In data-driven marketing, rather than relying on an executive’s best judgement, the plan is determined bycold, hard facts. It should come as no surprise that data-driven marketing would be of assistance to youre-commerce firm in increasing conversion rates, gaining insights for product development, andmonitoring consumer experiences. Putting this concept into action, however, is notoriouslychallenging.